Performance of the BinaxNOW coronavirus disease 2019 (COVID-19) Antigen Card test relative to the severe acute respiratory coronavirus virus 2 (SARS-CoV-2) real-time reverse transcriptase polymerase chain reaction (rRT-PCR) assay among symptomatic and asymptomatic healthcare employees. (25th January 2022) - James, Allison E.; Gulley, Trent; Kothari, Atul; Holder, Kasey; Garner, Kelley; Patil, Naveen
Abstract: The sensitivity of the BinaxNOW coronavirus disease 2019 (COVID-19) Ag Card test (BinaxNOW) was 51.6% among asymptomatic healthcare employees relative to real-time reverse transcriptase polymerase chain reaction (rRT-PCR). The odds of a positive BinaxNOW test decreased as cycle threshold value increased. BinaxNOW could facilitate rapid detection and isolation of asymptomatically infected persons in some settings while rRT-PCR results are pending.